A Comparison of Myrosinase Activity and Stability in Fresh Broccoli (B. oleracea var. Italica) and Brown Mustard (B. juncea) Seeds - Olukayode Adediran Okunade; Lisa Methven; Keshavan Niranjan (Turkish Journal of Agriculture: Food Science and Technology)
The effects of temperature and pressure processing on myrosinase extracted from fresh broccoli and brown mustard seed was studied. Brown mustard seeds had higher myrosinase activity (2.75 un/mL) than fresh broccoli (0.58 un/mL). The extent of enzyme inactivation increased with pressure (200-800 MPa) and temperature (30-80°C) for both brown mustard seeds and fresh broccoli myrosinase. However, at combinations of lower pressures (200-400 MPa) and temperatures (30-80°C), there was less myrosinase inactivation. When processing at a pressure of 300 MPa with a temperature of 70°C for 10 minutes, there was 65% myrosinase activity for brown mustard while at 300 MPa and 60°C, activity retention in fresh broccoli was 30%. Whereas, the corresponding activity retentions when applying only heat (70°C for 10 minutes) was 35% for brown mustard myrosinase, while there was no measurable myrosinase activity for fresh broccoli (60°C, 10 minutes). Thus, application of moderate pressures (200-400 MPa) on brown mustard and fresh broccoli can potentially be used to retain myrosinase activity needed for subsequent glucosinolate hydrolysis.